PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH KEBIJAKAN DIVIDEN - Halim, Danastia Vefiani; Wijaya, Henryanto (Jurnal Paradigma Akuntansi, 2024)
This research aims to determine the effect of liquidity, profitability and leverage on firm value moderated by dividend policy by using a sample of 23 family manufacturing companies listed on the IDX in 2018-2020. The data processing of this research uses Eviews 12. The results of this study indicate that liquidity has a negative and insignificant effect on firm value; profitability has a positive and significant impact on firm value; leverage has a positive and insignificant effect on firm value; dividend policy has a positive and insignificant effect; dividend policy does not have a significant and negative effect on the relationship between the influence of liquidity on firm value; dividend policy does not have a significant and positive effect on the relationship between profitability and firm value; dividend policy has no significant and negative effect on the relationship between leverage and firm value.